2005
DOI: 10.2190/v2n7-dmc4-2jwb-5q88
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Attitudes toward Web-Based Instruction May Not Be Enough: Limited Use and Obstacles to Implementation

Abstract: Data from 87 out of 250 faculty (34% response rate) responded to a two-page survey on Internet usage, attitudes, and perceived benefits and shortcomings. Overall, 73.6% of the faculty indicated a positive view of using the Internet for instructional purposes and 69.4% believed that the Internet is an effective teaching tool. However, only about one-half (47%) of our sample currently use online didactic approaches to present material in their courses. Also, 58.1% of faculty respondents indicated that they had e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…This appears to be compounded by confusion amongst academics and nurse educators about how best to facilitate such learning (Ip et al, 2007;Kenny, 2002;McVeigh, 2008). Furthermore, colleagues may not be sufficiently prepared or supported in carrying out these fairly demanding and timeconsuming processes and may need to engage with a whole new set of teaching and learning skills in order to do so (McPherson and Nunes, 2004;Vodanovich and Piotrowski, 2005). However, nurse educators have a key role to play in terms of modelling the significance of ICT and e-learning skills in relation to nursing practice, particularly in respect of data recording, managing information and developing information literacy skills.…”
Section: Ict Integrationmentioning
confidence: 99%
“…This appears to be compounded by confusion amongst academics and nurse educators about how best to facilitate such learning (Ip et al, 2007;Kenny, 2002;McVeigh, 2008). Furthermore, colleagues may not be sufficiently prepared or supported in carrying out these fairly demanding and timeconsuming processes and may need to engage with a whole new set of teaching and learning skills in order to do so (McPherson and Nunes, 2004;Vodanovich and Piotrowski, 2005). However, nurse educators have a key role to play in terms of modelling the significance of ICT and e-learning skills in relation to nursing practice, particularly in respect of data recording, managing information and developing information literacy skills.…”
Section: Ict Integrationmentioning
confidence: 99%
“…Research has suggested that the lack of more advanced applications of the Internet in the courses may be due to the lack of competence and proper training in such advanced applications (Vodanovich & Piotrowski, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the literature looking at the implementation ofWBIT focuses on faculty technology usage, faculty attitudes and concerns regarding the use of technology, and faculty perceptions toward the incorporation of technology into instruction (Aust, Newberry, O'Brien, & Thomas, 2005;Crooks, Yang, & Duemer, 2002;Inman & Mayes, 1998;Vodanovich & Piotrowski, 2005). Conversely, empirical research that examines institutional support concerning technology implementation in higher education has received significantly less attention.…”
Section: Distribution Of Computer Self-efficacy (Cse)mentioning
confidence: 99%
See 2 more Smart Citations